2010
DOI: 10.1002/bit.23002
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme identification and development of a whole‐cell biotransformation for asymmetric reduction ofo‐chloroacetophenone

Abstract: Chiral 1-(o-chlorophenyl)-ethanols are key intermediates in the synthesis of chemotherapeutic substances. Enantioselective reduction of o-chloroacetophenone is a preferred method of production but well investigated chemo- and biocatalysts for this transformation are currently lacking. Based on the discovery that Candida tenuis xylose reductase converts o-chloroacetophenone with useful specificity (kcat/Km=340 M(-1) s(-1)) and perfect S-stereoselectivity, we developed whole-cell catalysts from Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 37 publications
0
53
0
Order By: Relevance
“…In the context of chronic diseases such as aneurysms and skin aging, this rate is likely significant as GrB has a high affinity for PGs leading to its increased accumulation and cleavage would occur over a prolonged period of time in areas of extracellular GrB accumulation, as suggested in previous publications [9], [10]. In addition, several other proteases have been characterized to cleave substrates as similar rates, and have been determined to be catalytically efficient [38], [39], [40], [41], [42]. Nonetheless, future studies are necessary to examine GrB-mediated proteoglycan cleavage in vivo and to identify GrB-derived cleavage fragments in chronic human disease.…”
Section: Discussionmentioning
confidence: 83%
“…In the context of chronic diseases such as aneurysms and skin aging, this rate is likely significant as GrB has a high affinity for PGs leading to its increased accumulation and cleavage would occur over a prolonged period of time in areas of extracellular GrB accumulation, as suggested in previous publications [9], [10]. In addition, several other proteases have been characterized to cleave substrates as similar rates, and have been determined to be catalytically efficient [38], [39], [40], [41], [42]. Nonetheless, future studies are necessary to examine GrB-mediated proteoglycan cleavage in vivo and to identify GrB-derived cleavage fragments in chronic human disease.…”
Section: Discussionmentioning
confidence: 83%
“…It has been demonstrated that about 20% total cellular NAD(H) in wild-type cells is freely accessible and the (4). In several studies, the cellular cofactor concentration has been increased through manipulating the NAD ϩ biosynthetic pathway (12,16) or feeding permeabilized cells (18,36,37). The NAD(H) level was increased up to 6-fold previously (12).…”
Section: Discussionmentioning
confidence: 99%
“…Although many reductases efficiently mediate a variety of enantioselective bioconversion, the cofactor is too expensive for the enzymatic bioconversion to be performed economically [1,3]. To alleviate this cost factor, a cofactor recycling system is usually introduced to the reductase bioconversion: namely, the enzyme coupling reaction of glucose dehydrogenase (GDH) [4][5][6] or formate dehydrogenase (FDH) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%